Performance of a hybrid process integrating PAC adsorption with ceramic membrane ultrafiltration for drinking water treatment. Issue 5 (October 2022) - Wang, Mengen; Cen, Qihang; Zeng, Rong; Huang, Yidi; Liu, Yanling; Xia, Shengji
Abstract: Membrane separation technologies have broad application prospects in water treatment. Compared with polymeric membranes, ceramic membranes have higher stability for long-term operation in practical applications. Coupling ceramic membranes with other water treatment processes is an effective way to improve membrane treatment effect and alleviate membrane fouling. This study evaluated the water purification efficiency and membrane fouling behaviors of powdered activated carbon (PAC), flat-sheet ceramic membranes and their hybrid process in treating model organic pollutants and natural water. Results showed that the PAC-ceramic membrane hybrid process could alleviate the membrane fouling caused by humic acid but aggravate that caused by sodium alginate. Addition of PAC notably improved the removal performance of the ceramic membrane for organic matters in natural water as well as pharmaceutical and personal care products, and effectively controlled membrane fouling. The PAC adsorption obviously reduced the irreversible fouling of the ceramic membrane under multi-cycle operation. This study can provide a reference for the practical application of ceramic membranes in drinking water treatment. Graphical Abstract: ga1 Highlights: A novel hybrid process integrating adsorption with ceramic membranes was studied. The adsorption effectively alleviated the membrane fouling caused by humic acid. The hybrid process had enhanced removal effect on organic matter in natural water. Powdered activated carbon inhibited accumulation of irreversible membrane fouling.